Effect of growth regulators on sex expression and some quantitatve properties (Baghdad Science Journal, 2005)
This study was conducted in an orchard pomegranate's Department of Horticulture College of Agriculture, University of Baghdad for two seasons 1999-2000 on cultivars pomegranate Salimi and narrators seedless to study the effect spraying Nizant growth in sex ratio of flowers and recipes flowering and winning was selected 27 trees per class 15 years old planted